A new Chiasmocleis (Anura: Microhylidae) from the eastern Guiana Shield with an amended definition of C. haddadi Peloso, Sturaro, Forlani, Gaucher, Motta, & Wheeler, 2014 - Fouquet, Antoine; Rodrigues, Miguel T.; Peloso, Pedro (Zootaxa, 2022)
The existence of an unnamed (candidate) species from French Guiana and the state of Amapá (Brazil) closely related to Chiasmocleis haddadi has been hypothesized in previous DNA-based studies. With an integrative use of genetic, morphological and acoustic data we confirm that these populations are indeed distinct from C. haddadi and all other known congeners. We herein describe and name this new species, and amend the definition of C. haddadi since the type-series and its original diagnosis included specimens of the new species. Geographically, the new species occurs eastward of its sister species C. haddadi from which it can be distinguished by having a larger body, a proportionally smaller eye and a distinct dorsal colouration. We suspect that the new species breeds in the leaf litter and that tadpoles undergo endotrophic development whereas co-occurring C. haddadi and C. hudsoni lay clutches in the leaf litter nearby standing water of temporary ponds where exotrophic tadpoles complete their development. This new species is a new addition to the already long list of animals being endemic to the easternmost part of the Guiana Shield, a region identified as a singular bioregion within Amazonia by previous research.